2014
DOI: 10.1186/1477-7819-12-4
|View full text |Cite
|
Sign up to set email alerts
|

Poorly differentiated mesenteric carcinoma of unknown primary site detected by abscess formation: case report

Abstract: BackgroundCarcinoma of unknown primary site (CUP) is said to account for approximately 3 to 5% of all carcinomas. However, an isolated lesion in the abdominal cavity is rare, and there are no reports describing associated abscess formation.Case presentationA 76-year-old woman had consulted a previous physician complaining of fever and right lower quadrant abdominal pain. Enhanced computed tomography (CT) showed an abscess formation around the cecum. She was treated conservatively with antibiotics, but the symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…A previous study has presented a case of embryonal carcinoma originating in the mesentery (1). A further case study reported on poorly differentiated adenocarcinoma of unknown primary site detected by mesenteric abscess formation (2). The present case study reports on a case of PMA that was covered by an abscess of the mesocolon, and had the complication of intestinal obstruction.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study has presented a case of embryonal carcinoma originating in the mesentery (1). A further case study reported on poorly differentiated adenocarcinoma of unknown primary site detected by mesenteric abscess formation (2). The present case study reports on a case of PMA that was covered by an abscess of the mesocolon, and had the complication of intestinal obstruction.…”
Section: Introductionmentioning
confidence: 99%